Correction: An integrated group decision-making method under q-rung orthopair fuzzy 2-tuple linguistic context with partial weight information. - Fatima Abbas; Jawad Ali; Wali Khan Mashwani; Muhammad I Syam (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0297462.].